2017
DOI: 10.1002/2017ja024550
|View full text |Cite
|
Sign up to set email alerts
|

Lower Hybrid Drift Waves and Electromagnetic Electron Space‐Phase Holes Associated With Dipolarization Fronts and Field‐Aligned Currents Observed by the Magnetospheric Multiscale Mission During a Substorm

Abstract: We analyze two ion scale dipolarization fronts associated with field‐aligned currents detected by the Magnetospheric Multiscale mission during a large substorm on 10 August 2016. The first event corresponds to a fast dawnward flow with an antiparallel current and could be generated by the wake of a previous fast earthward flow. It is associated with intense lower hybrid drift waves detected at the front and propagating dawnward with a perpendicular phase speed close to the electric drift and the ion thermal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 75 publications
(136 reference statements)
3
40
0
Order By: Relevance
“…We have presented observations of EHs observed simultaneously at four MMS spacecraft in a region with intense parallel currents and fast plasma flows in the plasma sheet boundary layer. Similar EHs associated with intense parallel currents in the plasma sheet boundary layer have been recently reported by Le Contel et al (), but the spacecraft separation of about 50 km did not allow simultaneous observations of the EHs at four MMS spacecraft. We have used multispacecraft interferometry to estimate the EH velocities and direction of propagation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We have presented observations of EHs observed simultaneously at four MMS spacecraft in a region with intense parallel currents and fast plasma flows in the plasma sheet boundary layer. Similar EHs associated with intense parallel currents in the plasma sheet boundary layer have been recently reported by Le Contel et al (), but the spacecraft separation of about 50 km did not allow simultaneous observations of the EHs at four MMS spacecraft. We have used multispacecraft interferometry to estimate the EH velocities and direction of propagation.…”
Section: Discussionsupporting
confidence: 80%
“…For several of the EHs we have demonstrated that their 3‐D configuration is adequately described by Gaussian distributions with elliptic cross section and two perpendicular scales that can differ by as much as a factor of 3. Thus, in contrast to the assumption often invoked in single‐spacecraft studies (e.g., Chen et al, ; Le Contel et al, ; Vasko et al, ), the EHs are generally not axially symmetric. EHs exhibit d max / d ∥ ∼2–3 and d min / d ∥ ∼1–2 that is in satisfactory agreement with the gyrokinetic scaling relation (Franz et al, ) predicting d ⊥ / d ∥ ∼1.4–2.2 for ω p ∼ 1–2 ω c .…”
Section: Discussionmentioning
confidence: 83%
“…In the presence of high‐frequency wave activity, our averaged data processed beyond ion‐gyro time scales may smear out the responsible electric fields and may cause differences between the E × B drift and the electron motion in addition to the possible contribution from electron‐scale processes. Such wave activity was, however, weaker for event (ii) (Le Contel et al, ). The overall agreement between the electric‐field drift and electron perpendicular velocity shown in Figure , and the agreement between the curlometer current and the particle current during the intense dawn‐dusk current events indicated in Figure , suggested that the overall processes of these intense current events can be well described with Hall physics once different ion components are taken into account.…”
Section: Discussionmentioning
confidence: 96%
“…While we have so far concentrated on processes with ion scales or larger, the above description may need some modification once shorter time variations are taken into account. For example, the first type of Hall current described above contains highly structured electron currents due to interactions with lower‐hybrid waves, which was obtained based on the high‐resolutions particle and field data (Le Contel et al, ). In the presence of high‐frequency wave activity, our averaged data processed beyond ion‐gyro time scales may smear out the responsible electric fields and may cause differences between the E × B drift and the electron motion in addition to the possible contribution from electron‐scale processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation